The Past, Present, and Future of Mexico's National Bioethics Commission - de Chavez, Manuel Ruiz (The Hastings Center report, 2017)
The establishment of Mexico's National Bioethics Commission (Comisión Nacional de Bioética), in 1992, was conceived within the context of a global movement aimed at raising awareness of the ethical implications of technological and scientific development, especially in biomedicine. In 2005, a new decree put the commission under the scope of the Secretariat of Health and granted it technical and operational autonomy, allowing it to become a regulatory agency aimed at promoting a culture of bioethics, encouraging reflection on human health, and developing guidelines for health care, research, and education, through a global, secular, and democratic perspective. The commission became the leading actor in the strategy for institutionalizing bioethics in Mexico after reforms to the country's General Health Act in 2011, which required that public, social assistance, or private health care facilities establish a hospital bioethics committee to address bioethical dilemmas or issues and, when relevant, a research ethics committee to address research with human subjects. This assignment has shifted the focus of the activities and goals of the National Bioethics Commission toward establishing these committees in line with current regulations and developing mechanisms to ensure that they operate with the highest standards of ethical conduct, performance, and accountability.